The Role of Artificial Intelligence in the Evolution of Brand Voice in Multimedia - Surikova, Jūlija; Siroda, Sati; Bhattarai, Bharat (Molung Educational Frontier, 2022)
Digital automation and artificial intelligence (AI) have transformed over decades as more organizations communicate with audiences utilizing multimedia platforms globally. With digitalization, brand voice has become necessary in brand communication with users, and conversational AI interprets inputs. The aim is to explore how AI has evolved brand voice in multimedia and its interdependencies. Qualitative research design is applied based on content analysis of various multimedia applications. Initially, the role of AI in the evolution of brand voice, AI in multimedia, and the role of brand voice in multimedia were reviewed, highlighting the research gap. By drawing implications from shared study areas, the interdependence of these three notions was determined. This paper finds that AI plays a crucial role in evolving, developing, predicting, and analyzing brand voice in multimedia, resulting in the current life cycle of the brand voice. The interdependence diagram and brand voice life cycle reveal that AI defines brand voice's effectiveness and helps evolve it by offering suggestions. AI-powered engines are crucial to the success of multimedia platforms, and thus the paper introduces AI-powered two-way integration architecture.